Leopard and his spots - Harper, Kathryn (Cambridge : Cambridge University Press, 2016)
Leopard doesn't like his spots, can the doctor help him? A humourous story readers will love. In Red Band the sense of story starts to be developed. Illustrations continue to support understanding but readers also need to use decoding skills. Slightly longer texts with less repetition extend high-frequency word knowledge. Contains full teaching support including learning outcomes, curriculum links and follow-up activities.
Keywords: Children's - stories